IDENTIFIKASI RHODAMIN B DAN METHANYL YELLOW PADA MANISAN BUAH YANG BEREDAR DI KOTA BANDA ACEH SECARA KUALITATIF - Masthura, Masthura (Department of Chemistry, Faculty of Science and Technology, UIN Ar-Raniry, 2019)
Identification of Rhodamin B and methanyl yellow on fruit candies circulating in the city of Banda Aceh in a qualitative manner using the spot test method has been conducted which is chemical analysis using reagent kits. The principle of this test is by reacting a substance or sample with reagent (reagent kit) to determine the content of synthetic dyes from the substance or the sample is characterized by a distinctive color change. Samples of candied fruit obtained from traders who sell on Jl. Diponegoro, Jl. Teuku Umar, and Jl. Tgk Hasan Saleh. Based on the results of test, it can be concluded that all samples of candied fruit are yellow (liko kuning I, liko kuning II and mango) originating from Jl. Diponegoro, Jl. Teuku Umar, Jl. Tgk Hasan Saleh was not detected to contain methanyl yellow synthetic coloring, while for candied fruits that are red (liko merah I, liko merah II, nutmeg, sugar palm fruit and sago eyelets) there is one sample which contains rhodamine B, which is a sago eyelets.